THE DIAGNOSTIC VALUE OF COLPOSCOPY IN CERVICAL PATHOLOGIES - Toshboyeva Shohista Chorshanbi qizi; Allamurotova Fotima Tohir qizi; Axtamova Nilufar Akbarjanovna (GLOBAL SCIENTIFIC RESEARCH AND INTELLECTUAL PURSUITS, 2026)
This thesis evaluates the diagnostic efficacy of colposcopy in the early detection and management of cervical pathologies. By analyzing colposcopic findings and correlating them with histological outcomes, the study demonstrates that colposcopy is an indispensable clinical tool that bridges the gap between initial screening and definitive diagnosis. The findings emphasize that colposcopically directed biopsies significantly increase the accuracy of detecting cervical intraepithelial neoplasia (CIN) and early invasive cancer, thereby optimizing patient outcomes and preventing disease progression.